Penerapan Orbits Mode Data Fitting Untuk Kalibrasi Dipstick - Jovian Dian Pratama; A Nafis Haikal; Ratna Herdiana; Susilo Hariyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT The purpose of writing this article is to examine how mathematical literacy is during the Covid-19 period. The method used is to conclude theoretical studies by reviewing, analyzing, and concluding previous and developed research in the conditions of the Covid-19 pandemic. The author examines learning problems in the Covid-19 era related to mathematical literacy. The results of the study, mathematical literacy is related to real problems. The kinds of mathematical literacy are: spatial literacy, numeracy, and quantitative literacy or data literacy. In conclusion, the existence of learning barriers during the Covid-19 pandemic created solutions and learning strategies to improve mathematical literacy. Keywords: Covid-19, Mathematical Literacy, Pandemic